Implementation of Spousal Rights and Obligations in Kawin Turun Marriage, South Kotamobagu - Gavinna Mantali; Dolot Alhasni Bakung; Fitran Amrain (Journal of Law, Human Rights, Immigration, and Corrections, 2026)
This study examines how spousal rights and obligations are implemented in the Kawin Turun marriage practice in South Kotamobagu. Kawin Turun is a socially negotiated marriage conducted after premarital pregnancy, but the husband commonly leaves the wife after the marriage ceremony. Using empirical legal research with a qualitative approach, this study draws on interviews, observation, and legal materials concerning marriage law and customary practice. The findings show that the legal bond of marriage does not automatically produce substantive domestic life. The husband’s obligations to provide maintenance, protection, and residence are weakly fulfilled because economic readiness and cohabitation are absent. The wife’s domestic role is also constrained because household management occurs without spousal support. This gap reveals limited legal protection for women and children when customary settlement dominates formal marital obligations. The study concludes that Kawin Turun requires preventive legal education, Religious Affairs Office supervision, and community-based intervention by local institutions.